Grip strength predicts cardiac adverse events in patients with cardiac disorders: an individual patient pooled meta-analysis. Issue 11 (19th November 2018) - Pavasini, Rita; Serenelli, Matteo; Celis-Morales, Carlos A; Gray, Stuart R; Izawa, Kazuhiro P; Watanabe, Satoshi; Colin-Ramirez, Eloisa; Castillo-Martínez, Lilia; Izumiya, Yasuhiro; Hanatani, Shinsuke; Onoue, Yoshiro; Tsujita, Kenichi; et al.
Abstract : Objective: Grip strength is a well-characterised measure of weakness and of poor muscle performance, but there is a lack of consensus on its prognostic implications in terms of cardiac adverse events in patients with cardiac disorders. Methods: Articles were searched in PubMed, Cochrane Library, BioMed Central and EMBASE. The main inclusion criteria were patients with cardiac disorders (ischaemic heart disease, heart failure (HF), cardiomyopathies, valvulopathies, arrhythmias); evaluation of grip strength by handheld dynamometer; and relation between grip strength and outcomes. The endpoints of the study were cardiac death, all-cause mortality, hospital admission for HF, cerebrovascular accident (CVA) and myocardial infarction (MI). Data of interest were retrieved from the articles and after contact with authors, and then pooled in an individual patient meta-analysis. Univariate and multivariate logistic regression was performed to define predictors of outcomes. Results: Overall, 23 480 patients were included from 7 studies. The mean age was 62.3±6.9 years and 70% were male. The mean follow-up was 2.82±1.7 years. After multivariate analysis grip strength (difference of 5 kg, 5× kg) emerged as an independent predictor of cardiac death (OR 0.84, 95% CI 0.79 to 0.89, p<0.0001), all-cause death (OR 0.87, 95% CI 0.85 to 0.89, p<0.0001) and hospital admission for HF (OR 0.88, 95% CI 0.84 to 0.92, p<0.0001). On the contrary, we did not find any relationship between grip strength and occurrence of MI or CVA. Conclusion: In patients with cardiac disorders, grip strength predicted cardiac death, all-cause death and hospital admission for HF. Trial registration number: CRD42015025280.